ANALISIS ASUHAN KEPERAWATAN DENGAN INTERVENSI INOVASI TERAPI MUSIK PADA PENDERITA HIPERTENSI YANG MENGALAMI KECEMASAN DI KELURAHAN SUKAMAJU BARU, KOTA DEPOK. - Christin Maria (2022)
Hypertension is a chronic disease that is manifested by an increase in blood pressure above the normal range. The results of the 2015 WHO report show that there are 1.3 billion people in the world suffering from hypertension and the prevalence of hypertension is estimated to increase until 2025, which is 1.5 billion or around 29% of the world's population (Yulastari, Betriana, & Kartika, 2018). One of the psychological effects felt by people with hypertension is anxiety. In treatment, the therapy that is often used is music therapy. Music therapy is a therapy that uses music as a healing medium to support the client's health. This analysis uses the literature review method and provides direct music therapy interventions to 2 samples consisting of 1 managed patient and 1 resume patient. The purpose of this scientific work is to review the effectiveness of music therapy in reducing anxiety in hypertensive patients. At the beginning of the study, both patients had scores from the Hamilton Rating Scale For Anxiety (HARS) questionnaire, which were 27 for managed patients and 25 for resume patients who were included in the moderate anxiety category. After performing music therapy on managed patients and resume patients, the results showed that the client experienced a decrease in anxiety levels from the moderate anxiety category to the mild anxiety category.